Victor Hugo (1802-1885-1985) - Charó, René (Revista Chilena de Humanidades, 2016)
A hundred years after the death of Víctor Hugo, Prof. Charó places the great French writer in bis own epoch as well as in relation to our own . His epic, lyri cal and satirical poetry, his dramatic works and his novels, are commented upon and compared to the works of other authors. On the other hand, Prof. Charó outlines Víctor Hugo’s philosophical and polítical ideas, together with the criticism of his adversaries. This study closes with brief remarks upon the French writer’s memoirs.